Whorf's Lost Argument: Multilingual Awareness. Issue 3 (23rd June 2016) - Pavlenko, Aneta
Abstract : Debates about linguistic relativity commonly focus on one question: Does language affect thought? This yes‐or‐no question does not do justice to the complexity of Whorf's ideas and skirts several issues of great importance to Whorf. My first aim in this article is to recover the arguments that got lost in translation of Whorf's ideas into the Sapir‐Whorf hypothesis. I will show that, for Whorf, languages were also one of the ways in which we think, scientists were not immune to language effects, and the key to advancement of Western science was multilingual awareness. My second aim is to draw on these insights to articulate a Whorfian agenda for the field of second language acquisition (SLA) that asks new questions about second language learning and cognition and expands the boundaries of the field and the scope, duration, and locations of SLA research.